Workplace Factors Shaping Employee Performance in Public Institutions: Faktor Tempat Kerja yang Mempengaruhi Kinerja Karyawan di Lembaga Publik - Fatma, Salsabila Nur Tsabita; Prapanca, Detak; Sari, Herlinda Maya Kumala; Firdaus, Vera (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Employee performance is a crucial element in achieving organizational goals, particularly in public institutions. Specific Background: Prior studies highlight the roles of work environment, motivation, and discipline, yet inconsistencies remain across organizational contexts. Knowledge Gap: Limited empirical evidence examines these variables simultaneously within local governmental offices. Aim: This study aims to analyze how work environment, work motivation, and work discipline contribute to employee performance. Results: Findings indicate that all three variables show significant positive relationships with performance, with work discipline emerging as the strongest predictor. Novelty: The study provides updated empirical insight from a public-sector context rarely explored in recent literature. Implications: The results suggest that strengthening discipline policies, improving work conditions, and maintaining motivational programs can enhance organizational productivity. Highlights:• Significant role of work environment• Strong contribution of work discipline• Motivation supporting employee performance Keywords: Work Environment, Work Motivation, Work Discipline, Employee Performance, Public Institution